Sistem pengolahan lahan tanpa bakar dalam kebakaran hutan dan lahan pada kawasan gambut Kecamatan Bukit Batu Kabupaten Bengkalis - Febri Yuliani; Saktioto Saktioto; Rosnita Rosnita; Eka Armas Pailis; Murniati Murniati; Idjang Tjarsono (Unri Conference Series: Community Engagement, 2019)
Forest fires are a crucial problem and need to be taken seriously, because these fires, besides causing environmental disruption from smoke, also result in loss of forest potential and biodiversity degradation. Therefore it is necessary to do an effective and efficient forest fire control effort. Bengkalis Regency is one of the regencies in Riau Province. In the Binaan Village activity that will be carried out is in Bukit Batu District, this is done considering that Bukit Batu District has the potential to develop various economic and social aspects and with extensive peat conditions, this is what attracts the Riau University community service team to conduct the Binaan Village in the region the. Identification of problems include: institutions that have not been optimal and the lack of seriousness of the government and farmer groups to implement a non-burning land management system in dealing with forest and peatland fires in peat areas caused by lack of information and technology and institutions in non-burning land management. The purpose of this activity is: Improving the skills of the community in the Bukit Batu District of Bengkalis Regency so that they can apply techniques to open agricultural land without burning, water management, and agricultural cultivation on peatlands, as well as harvesting and post-harvesting. Improve community skills so that they can strengthen institutions, business and market analysis, and the growth of entrepreneurial spirit. The dedication method is carried out in several stages, namely: (1) Preparation Phase, (2) Work Program Preparation Phase, (3) Workshop Implementation Stage, (4) Assistance Implementation Stage, (5) Program Monitoring and Evaluation Stage, and (6) Reporting Phase. From the devotion of the Fostered Village it is known that: forest and land fires are not solely due to natural factors such as drought. Natural factors provide conditions for fires to occur, but humans also play an important role. Human-caused forest fires occur due to activities Local communities have a very substantial control role in village development because control of the decision-making process must be given to those who later bear the consequences of development including failure or negative impacts that occur due to village development. Therefore, decision making authority must be given to local communities. The parameter of community participation in supervision is involvement in the supervision team and their authority.